Polymorphism in Superoxide Dismutase, Catalase Genes and Their Role in Cervical Cancer Susceptibility among Rural Population of Maharashtra: Findings from A Hospital based Case Control Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The present study was planned to investigate the possible association between polymorphismsof superoxide dismutase, SOD1 (Cu,Zn-SOD), SOD2(Mn-SOD), SOD3(EC-SOD) and catalase genes andthe risk of cervical cancer in rural population of Maharashtra.Methods: A case control study included 350 proven cervical cancer cases and 400 healthy age matchedcontrol women. Genotyping of isoforms of SOD and CAT were done by polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) method.Results: When we studied genotype frequencies of codon 326 and 262 region of promoter of CAT gene,there was no significant association between A to T transition at codon 326 (p=0.45) and CAT C262Tpolymorphism (p=0.30) with susceptibility to cervical cancer. The variant G allele of SOD1 at codon 251significantly increased in cervical cancer patients as compared with the control women (OR=3.02, 95% CI:1.72-5.31; p
Keywords: Genetic polymorphism, Superoxide dismutase, Catalase, Cervical cancer.